Highly efficient povidone-phosphotungstic acid catalyst for the tandem acetalization of aldehydes to bis- and tris(indolyl)methanes - Kamble, Sumit B.; Swami, Rameshwar K.; Sakate, Sachin S.; Rode, Chandrashekhar V. (ChemPlusChem, 2013)
A novel, nonleachable hybrid of heteropoly acid and polyvinylpyrrolidone (or povidone) catalyzes the acetalization of aldehydes in methanol at room temperature followed by reaction with indole to give bis(indolyl)methanes (BIMs) and tris(indolyl)methanes (TIMs) in quantitative yields (90-97%). The catalyst was shown by pyridine FTIR spectroscopy to possess BrOnsted acidity, and the hybrid formation was confirmed by XRD and (PNMR)-P-31 studies. Friedel-Crafts alkylation of indole as well as the tandem synthesis of BIMs and TIMs were established with several types of carbonyl and indole substrates to give the corresponding products quantitatively. The catalyst was recycled efficiently for three successive runs without losing its original activity.
Keywords: acetals; Acidity; aldehydes; heterogeneous catalysis; heteropoly acids

Single pot conversion of furfuryl alcohol to levulinic esters and gamma-valerolactone in the presence of sulfonic acid functionalized ILs and metal catalysts - Hengne, Amol M.; Kamble, Sumit B.; Rode, Chandrashekhar V. (Green Chemistry, 2013)
Ionic liquids functionalized with acidic anions, HSO4, ClSO3H, PTSA, TFA (MIm), HSO4 and TFA (NMP) were found to efficiently (99% conversion) catalyze the alcoholysis of furfuryl alcohol (FAL) in the presence of methanol, ethanol, n-butanol and isopropyl alcohol (IPA) to the corresponding levulinic acid esters under mild temperature (90-130 degrees C) conditions. The extended alkyl chain length of [MIm] using 1,4-butane sultone enhanced the Bronsted acidity of [BMIm-SH][HSO4] catalyst resulting into the highest selectivity of >95% to Me-LA. An increase in both temperature and catalyst concentration increased the furfuryl alcohol conversion and selectivity to levulinate esters. In contrast, an increase in the substrate concentration from 5 to 15% caused a decrease in Me-LA selectivity due to accumulation of intermediate ethers of furfuryl alcohol. Using a combination of [BMIm-SH][HSO4] and 5% Ru/C catalyst, direct conversion of FAL to gamma-valerolactone (GVL) is shown for the first time. A complete conversion of FAL with the highest selectivity of 68% to GVL could be achieved under optimum conditions while higher Ru loading enhanced the GVL selectivity to 94% in the hydrogenation step of this tandem approach. Our catalyst system could be efficiently recycled five times retaining the original activity and selectivity levels.

Highly efficient triphenyl(3-sulfopropyl)phosphonium functionalized phosphotungstic acid on silica as a solid acid catalyst for selective mono-allylation of acetals - Kamble, Sumit B.; Shinde, Suhas H.; Rode, Chandrashekhar V. (Catalysis Science & Technology, 2015)
Silica supported phosphotungstic acid functionalized with triphenyl(3-sulfopropyl)phosphonium (PW-Si/TPSP) was developed as a solid acid catalyst for C-C bond formation via Hosomi-Sakurai allylation of acetals. Functionalization of PW as well as its binding to silica was confirmed by solid state P-31-NMR and Si-29-NMR, respectively. Among the various catalysts prepared, the 30% PW loaded (30PW-Si/TPSP) catalyst gave an excellent yield of homoallyl ethers (HAEs) via selective mono-allylation of acetals with allyltrimethylsilane. A plausible reaction pathway has also been proposed in which the strong Bronsted acid sites of 30PW-Si/TPSP play an important role in activating the acetals to form the corresponding oxonium cations. The versatility of our catalyst was demonstrated for the allylation of a wide variety of acetals while its stability was established in five successful recycling runs.

Cascade synthesis of 2-cyanoacrylamides through deacetalization and/or knoevenagelcondensation followed by selective monohydration of acetals and aldehydes over solid acidferrites - Kamble, Sumit B.; Rode, Chandrashekhar V. (Chemcatchem, 2016)
A new protocol of cascade synthesis for biologically active 2-cyanoacrylamides (1) was developed. The reaction proceeds over a novel magnetically retrievable solid-acid composite of iron oxide, poly(vinylpyrrolidone) and phosphotungstic acid (Fe3O4/PVP-PWA) in AcOH-H2O medium under reflux conditions. This transformation is facilitated through single-site Bronsted acid catalyzed cascade reactions involving deacetalization and/or Knoevenagel condensation followed by selective monohydration of nitriles starting from acetals (5) and aldehydes (2) with malononitrile (3). A series of aldehydes, dimethyl and diethyl acetals, along with some heterocyclic aldehydes were successfully transformed to 2-cyanoacrylamides with >95% yields. TEM images confirmed the coating of the PVP over nanosized Fe3O4. Stereoselective monohydration of 2-benzylidenemalononitriles (4) to E isomers was demonstrated by NOESY experiments. The catalyst could be efficiently recycled seven times on employment of both acetals and aldehydes as substrates, as a result of its magnetic nature.

MCM-41-supported phosphotungstic acid-catalyzed cleavage of C-O bond in allyl aryl ethers - Sakate, Sachin S.; Kamble, Sumit B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (New Journal of Chemistry, 2017)
Removal of the protecting allyl group from allyl aryl ethers in the presence of other oxygen protecting groups was successfully achieved using a solid acid supported on the high surface area material MCM-41. The catalyst showed excellent activity in the presence of various electron withdrawing, electron donating, and oxidizable functional groups. The methodology is also very useful for the removal of protecting allyl groups of various natural products such as vanillin, isovanillin, and other oxygen functionalized aldehydes and ketones.